An enhanced host–guest electro‐optical polymer system using poly(norbornene‐dicarboximides) via ROMP. Issue 6 (26th December 2012) - Yu, Feng; Spring, Andrew M.; Li, Lu; Qiu, Feng; Yamamoto, Kazuhiro; Maeda, Daisuke; Ozawa, Masaaki; Odoi, Keisuke; Yokoyama, Shiyoshi
Abstract High glass transition temperature poly(N‐cyclohexyl‐5‐norbornene‐2, 3‐dicarboximide)s (NDI)s prepared by ring opening metathesis polymerization yielded polymers with a narrow polydispersity and well‐controlled molecular weight materials when using the Grubbs first generation initiator. Polymers produced using the Grubbs second generation initiator could not be controlled easily. By initiator selection it was also possible to synthesize polymers with either 98 or 52% trans microstructures. These materials were employed as electro‐optic (EO) polymer hosts for high molecular hyperpolarizability (β) phenyl vinylene thiophene vinylene bridge chromophores. This chromophore was modified by the incorporation of a tert‐butyldiphenylsilane group. The addition was able to further increase its EO coefficient (r33) to reach 93 pm/V in a trans rich poly(NDI) produced by the Grubbs first generation initiator, compared to a benchmark chromophore / polymer combination. We investigated in detail the relationship between polymer microstructure and their absolute molecular weight on forming the best host–guest with the high β chromophore. Our results indicate that by utilizing a very simple host–guest system a high r33 can be realized. © 2012 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013